PENERAPAN HUKUM KELUARGA ISLAM PADA FASE PENJAJAHAN DAN KESULTANAN - Nyiwulan, Nyiwulan (An Nawawi, 2022)
The law during the colonial and sultanate periods in Indonesia already existed and has even been practiced by the community, this can be seen by the establishment of legal theory forms ranging from creed theory, receptio in complex theory to receptie theory. The legal form of the creed theory and the theory of receptio in complex during the sultanate period had been applied before the colonialists came, so that there was an attempt at legal intervention from the Netherlands against Islamic law by confronting customary law by establishing the receptie theory. The application of Islamic family law sociologically becomes a reference for values ​​that are believed to anticipate the development of all fields, philosophically it has become a positive law in the Indonesian legal system which has been applied legally legally, culturally it still exists even though it is no longer a form of the legal system. Due to the influence of Dutch legal intervention, Islamic family law is no longer a complete positive law because it has experienced a mixture of legal sources, such as the unification and codification of law.